Directions of graduation projects for students of the Department of Performing Arts between theory and practice (Journal of the College of Basic Education, 2023)
The directive directions are a process of pictorial writing to reshape the space of the reading text. It is a process of sensory-mental dialogue at the levels of the dramatic text to transform it into creative compositions subject to intentional and conscious artistic intent. Its purpose is to reformulate the vision of theatrical embodiment with vibrant artistic tools. (Space-philosophical-aesthetic), which reveals the direction of the scientific institution, especially the artistic institution that adopts an educational philosophy of its own, and this philosophy imposes on it a scientific-aesthetic approach that is consistent with its scientific orientations.It represents its means of consolidating knowledge information through the development of scientific curricula that are divided between the theoretical (aesthetic) axis and the applied (project) axis. Therefore, it is assumed that there will be a cognitive structure that runs in a parallel line to demonstrate the effectiveness of the aesthetic foundation and its impact on establishing the applied side of this knowledge, as the side represents Applied The applied space of the theoretical material as the laboratory that reveals the extent of the effectiveness of the theoretical material and its ability to achieve its aesthetic goal through the project or its failure. On the role of the theoretical-aesthetic material in updating the student's scientific and artistic skill, and thus placing him on the path of the correct scientific path that agrees with the direction of the scientific institution. The beautiful between aesthetic theorizing and applied space. This is why the research title came: (Project trends of students of the Department of Performing Arts between theory and practice).